FOREIGNIZATION AND DOMESTICATION IN THE TRANSLATION OF ENGLISH TECHNICAL TERMS -"ARCHITECTURE; FORM, SPACE AND ORDER" - Aprilianti, Novia (2014)
This research attempts to investigate the foreignization and domestication process in Indonesian version of the Architecture: Form, Space and Order book in terms of its strategies. This research aims to explore the categories of English architectural terms in the book and to find whether the English architectural terms are domesticated or foreignized in the Indonesian version of the book. This research uses descriptive design. A printed original version of the book and a PDF document Indonesian version of the book are the subjects of the research. The collected data is analyzed using Pedersen's (2005) continuum of foreignization - domestication and Baker's (1992) translation strategies. The result of the research indicates that there were 147 (76.17%) architectural terms of word level and 46 (23.29%) architectural terms of above word level.There were 38.33% of architectural terms translated by using domesticating strategies and 61.67% by using foreignizing strategies. This indicates that the English architectural terms in the Indonesian version is foreignized. Keywords: foreignization and domestication, architectural terms. Penelitian ini mencoba mengkaji tentang proses strategi foreinnisasi dan domestikasi pada buku Architecture: Form, Space and Order versi Bahasa Indonesia. Penelitian ini bertujuan untuk mengetahui kategori istilah arsitektural berbahasa Inggris pada buku tersebut dan untuk mengetahui apakah istilah-istilah arsitektural berbahasa Inggris pada buku versi Bahasa Indonesia diforeinnisasi atau didomestikasi. Penelitian ini menggunakan desain deskriptif. Buku asli dalam bentuk cetak dan buku versi Bahasa Indonesia dalam bentuk dokumen PDF menjadi subject dalam penelitian ini. Data yang tekumpul dianalisis menggunakan rangkaian kesatuan foreinnisasi - domestikasi Pedersen (2005) dan strategi penerjemahan Baker (1992). Hasil dari penelitian ini menunjukkan bahwa ada 38.33% istilah-istilah arsitektural yang diterjemahkan menggunakan strategi-strategi domestikasi dan 61.67% yang menggunakan strategi-strategi foreinnisasi. Ini menunjukkan bahwa istilah-istilah arsitektural berbahasa Inggris pada buku versi Bahasa Indonesia diforeinnisasi. Kata kunci: foreinnisasi dan domestikasi, istilah arsitektural